Galvanic Vestibular Stimulation Improves Spatial Cognition After Unilateral Labyrinthectomy in Mice - Nguyen, Thanh Tin; Nam, Gi-Sung; Kang, Jin-Ju; Han, Gyu Cheol; Kim, Ji-Soo; Dieterich, Marianne; Oh, Sun-Young (Frontiers in Neurology, 2021)
Objectives: To investigate the deficits of spatial memory and navigation from unilateral vestibular deafferentation (UVD) and to determine the efficacy of galvanic vestibular stimulation (GVS) for recovery from these deficits using a mouse model of unilateral labyrinthectomy (UL). Methods: Thirty-six male C57BL/6 mice were allocated into three groups that comprise a control group and two experimental groups, UVD with (GVS group) and without GVS intervention (non-GVS group). In the experimental groups, we assessed the locomotor and cognitive behavioral function before (baseline) and 3, 7, and 14 days after surgical UL, using the open field (OF), Y maze, and Morris water maze (MWM) tests. In the GVS group, the stimulations were applied for 30 min daily from postoperative day (POD) 0–4 via the electrodes inserted subcutaneously close to both bony labyrinths. Results: Locomotion and spatial cognition were significantly impaired in the mice with UVD non-GVS group compared to the control group. GVS significantly accelerated recovery of locomotion compared to the control and non-GVS groups on PODs 3 (p < 0.001) and 7 (p < 0.05, Kruskal–Wallis and Mann–Whitney U tests) in the OF and Y maze tests. The mice in the GVS group were better in spatial working memory assessed with spontaneous alternation performance and spatial reference memory assessed with place recognition during the Y maze test than those in the non-GVS group on POD 3 (p < 0.001). In addition, the recovery of long-term spatial navigation deficits during the MWM, as indicated by the escape latency and the probe trial, was significantly better in the GVS group than in the non-GVS group 2 weeks after UVD (p < 0.01). Conclusions: UVD impairs spatial memory, navigation, and motor coordination. GVS accelerated recoveries in short- and long-term spatial memory and navigation, as well as locomotor function in mice with UVD, and may be applied to the patients with acute unilateral vestibular failure.